Faint (and bright) variable stars in the satellites of the Milky Way - Vivas A. Katherina (EPJ Web of Conferences, 2017)
I describe two ongoing projects related with variable stars in the satellites of the MilkyWay. In the first project, we are searching for dwarf Cepheid stars (a.k.a δ Scuti and/or SX Phe) in some of the classical dwarf spheroidal galaxies. Our goal is to characterize the population of these variable stars under different environments (age, metallicity) in order to study their use as standard candles in systems for which the metallicity is not necessarily known. In the second project we search for RR Lyrae stars in the new ultra-faint satellite galaxies that have been discovered around the Milky Way in recent years.